Connecting the Dot: Understanding the Link between Secondary School Heads' Leadership Styles and Teacher Performance - Nasim, Farhat; Khurshid, Khalid; Akhtar, Samina; Kousar, Farzana (Pakistan Journal of Humanities and Social Sciences, 2023)
School Heads assume the ultimate obligation of accountability for student Academic excellence and teachers' performance in their institutions. The current Research exploration endeavored to analyze how the different leadership styles of school heads affect the performance of their teachers at public secondary schools in Multan. A descriptive research approach was employed in the current investigation. Data was collected using a questionnaire from a sample of four hundred and nineteen (419), including 187 male and 232 female teachers selected through stratified random sampling from secondary schools in the district of Multan, South Punjab, Pakistan. According to key highlighted observations of the study, Heads practiced all mixed leadership styles according to contextual requirements. However, no statistically significant differences were observed between teachers in terms of their professional and academic backgrounds or on the basis of their teaching experience. Moreover, according to manifested results, teachers' performance varied significantly according to their locations and gender. This study may help identify leadership approaches that inspire and empower teachers, leading to higher levels of productivity and overall job performance. Additionally, it is recommended that training for cultivating leadership styles that positively impact teacher performance be provided in educational institutions.